Atlas Florae Europaeae notes 32. The revised identity of Sorbus lanuginosa (Rosaceae) - Sennikov, Alexander N.; Somlyay, Lajos (Phytotaxa, 2018)
The infraspecific variability of common rowan, Sorbus aucuparia Linnaeus (1753: 477) (Rosaceae), is extensive and puzzling. In Europe, populations from some higher mountains and the arctic zone are commonly separated as S. aucuparia subsp. glabrata (Wimmer & Grabowski 1829: 21) Hedlund (1901: 45) on the basis of its nearly glabrous leaves with more serrate dentation (Meusel et al. 1965; Warburg & Kárpáti 1968; Mossberg & Stenberg 2003), although intermediate forms are common with the type subspecies, S. aucuparia subsp. aucuparia, which is characterized by regularly hairy leaves with more obtuse dentation (Vuokko & Hämet-Ahti 1998).